1994
DOI: 10.2190/1206-9618-dfj2-m6tx
|View full text |Cite
|
Sign up to set email alerts
|

Peace Corps Service as a Turning Point

Abstract: This is a longitudinal study of twenty-one U.S. Peace Corps Volunteers, first interviewed in the mid-1960s during their tour of service in the Republic of the Philippines and then twenty years later as middle-aged adults. Life events reported after their service and the high degree of response agreement in the two interviews confirm that their Peace Corps experience constituted a turning point in their life courses. The study reviews the literature on turning points, proposes an appropriate definition for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…In line with this, the current study adopts the view that the turning point does not refer to any strictly specified period of time or any one particular event; instead, the turning point is more of an indefinite "process of becoming," involving a plentitude of changes that takes place within a phase in the career of one's leisure pursuit. This view is in contrast with prior conceptualizations (e.g., Starr, 1994;Wethington, 2005), which most often seem to consider turning points as very specific events in the human life course, such as getting married or moving away from home. To illustrate, the main data generation phase of the present study took the form of autoethnography over a two-year period (2005)(2006)(2007), and more informal data have been accumulated since then.…”
Section: Introductioncontrasting
confidence: 72%
See 2 more Smart Citations
“…In line with this, the current study adopts the view that the turning point does not refer to any strictly specified period of time or any one particular event; instead, the turning point is more of an indefinite "process of becoming," involving a plentitude of changes that takes place within a phase in the career of one's leisure pursuit. This view is in contrast with prior conceptualizations (e.g., Starr, 1994;Wethington, 2005), which most often seem to consider turning points as very specific events in the human life course, such as getting married or moving away from home. To illustrate, the main data generation phase of the present study took the form of autoethnography over a two-year period (2005)(2006)(2007), and more informal data have been accumulated since then.…”
Section: Introductioncontrasting
confidence: 72%
“…Starr (1994) summarizes that the prior literature sees turning points as critical changes during which individuals adopt a new social role that is connected to a new set of people and a new self-conception involving a break with the past. In general, prior research perceives turning points as major transitions in life (Starr, 1994;Wethington, 2005); in the current study, the concept is applied to a subcultural setting. The abovementioned features of the turning point highlight how this point appears as a new beginning in one's leisure participation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploring the impacts on the GRP volunteers' lives, it was found that six volunteers experienced major changes, such as finding a career direction, or meeting a new partner and permanently relocating to Thailand, and these changes were described as 'life turning points' (Starr 1994). While there was little evidence that many other volunteers had, or expected to, change their daily lives in any considerable way, most volunteers identified some form of personal change as a result of their experiences at the GRP.…”
Section: Discussionmentioning
confidence: 99%
“…Often, volunteers are living outside of their country and culture for the first time, possibly learning another language, interacting with people who are different from themselves, and engaging in demanding, rewarding, and fulfilling work. The potential is high, therefore, for IVS to be a transformative experience in the lives of volunteers (Starr 1994;Grusky 2000;Hudson and Inkson 2006;Fantini with Tirmizi 2007).…”
Section: Ivs Volunteer Outcomesmentioning
confidence: 99%